Primary Posterior Sagittal Anorectoplasty in male neonates with Anorectal Malformations: A tertiary care hospital experience - Charu Tiwari; Neha S Shenoy; Suraj Gandhi; Apoorva Makan; Syamantak Basu; Akruti Tulsian; Hemanshi Shah (EL-Med-Pub, 2021)
Background: The conventional surgical management for a male neonate with intermediate Anorectal Malformation (ARM) involves three stages - the creation of a diversion stoma in the neonatal period, a definitive pull-through procedure/ Posterior Sagittal Anorectoplasty (PSARP) followed by stoma closure. With this background, we present our experience with Single-stage primary definitive repair in selected male neonates with ARM. Methods: Medical records of male ARM cases managed from 2016 to 2018 were reviewed. Male neonates who underwent primary PSARP were analysed retrospectively. Results: A total of 35 records were found, out of which 12 male neonates underwent primary PSARP. The      median gestational age and birth weight were 36.7 weeks and 2.75 kg respectively. Fistula with urinary tract was documented in all. The mean operative time was      65 minutes +/- 15 minutes. Two neonates had minor superficial surgical site infection at neo-anus. Anal dilatations were started after 2 weeks. At follow-up period of 3 years, 11 patients were continent; one patient had constipation with pseudo-incontinence which was successfully being managed by bowel management programme. Conclusions: A primary definitive procedure is feasible when performed on carefully selected male neonates with ARM and also avoids the morbidity of stoma and multiple surgeries and follow-up visits to hospitals.